Анализ методов и средств реализации алгоритмов распознавания образов по видеоизображению - Заворотна, М. Г.; Семенець, В. В. (ХНУРЕ, 2019)
Currently, in the field of computer vision technology of autorecognition and image tracking is a significant interest for scientific research. The main factors for increasing interest in this topic are a large number of scientific studies that create the basis for developments in this field and further study it. Over the past few years, clear results have been obtained in the actual application of methods for recognizing flying objects. The evolution of hardware and the growth of computing power of modern electronics, and the popularity of cloud services, makes it possible to actively use software based on computer vision algorithms, not only in the field of scientific and engineering activities, but also in the defense sector.
Keywords: розпізнавання образів; відеозображення; ПЛІС; Xilinx; FPGA; метод розпізнавання образів; алгоритм розпізнавання образів